2021
DOI: 10.1021/acschemneuro.0c00544
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin and Plycyrrhetinic Acid Synergistically Alleviate MPP+/MPTP-Induced Oxidative Stress through Nrf2-Dependent Glutathione Biosynthesis Mechanisms

Abstract: Recently, combination therapy has proven to be an effective strategy for treating polygenic/multifactorial/complex disorder such as Parkinson’s disease (PD). Here, we hypothesized that dual up-regulation of glutamate cysteine ligase (GCL) catalytic subunit (GCLc) and GCL modifier subunit (GCLm) via nuclear factor E2-related factor (Nrf2) contribute to the antioxidant effect of paeoniflorin (PF) synergistically with glycyrrhetinic acid (GA) (henceforth called PF/GA) in the context of MPP+/MPTP neurotoxicity. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…These results demonstrated that paeoniflorin effectively attenuated MPTP-induced motor impairment and DAn death. The neuroprotective effects of paeoniflorin observed in our study are consistent with those observed in previous studies [13,14,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results demonstrated that paeoniflorin effectively attenuated MPTP-induced motor impairment and DAn death. The neuroprotective effects of paeoniflorin observed in our study are consistent with those observed in previous studies [13,14,25].…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown to be a potential therapeutic target for alleviating oxidative stress in neurotoxin-induced PD [12]. Previous studies have suggested that the neuroprotective effects of PF in 1-methyl-4-phenyl- pyridinium/1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPP + /MPTP)-induced PD models may be mediated through activation of the α-synuclein/protein kinase C subtype-σ signaling pathway and Nrf2-dependent glutathione mechanisms [13,14]. However, whether PF relieves PD by alleviating oxidative stress-induced injury via the Nrf2 pathway is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of OS existing in PD is further supported by PD animals modeled with toxins that can cause OS, which includes 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) ( Dong et al, 2021 ), rotenone ( Sharma et al, 2021 ), paraquat ( Ahmad et al, 2021 ), and 6-hydroxydopamine (6-OHDA) ( Zou et al, 2021 ). Moreover, in vivo observations revealed that several markers of OS are altered in the cerebrospinal fluid and blood samples of PD patients ( Vinish et al, 2011 ).…”
Section: The Role Of Oxidative Stress In Parkinson’s Diseasementioning
confidence: 99%
“…Upon entry into cells, the neurotoxin MPTP is rapidly converted into the metabolite MPP + , and MPP+ enters dopaminergic neurons to stimulate oxidative stress and activate cell death signals. [ 55 ] A large number of studies on postmortem brain tissues of PD patients have shown that increased levels of mitochondrial complex I activity, SOD activity, and free iron levels and decreased levels of GSH level and antioxidant enzyme activity (such as CAT and GPx) could be observed in the SN of PD patients. [ 56 ] Damaged mitochondria can lead to the excessive production of ROS and the deposition of toxic wastes in the brain, which further lead to dopaminergic neuron death.…”
Section: Discussionmentioning
confidence: 99%